2016
DOI: 10.1021/acs.orglett.6b00999
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroform-Derived CuCF3 for Trifluoromethylation of Terminal and TMS-Protected Alkynes

Abstract: An efficient trifluoromethylation reaction of alkynes using a fluoroform-derived CuCF3 reagent is described. The CF3 source is the inexpensive industrial waste fluoroform (CF3H). The air-stable CuCF3 reagent can be prepared in large quantities and is convenient to use. Synthetically useful trifluoromethylated alkynes containing a wide range of functional groups were successfully synthesized under mild conditions. Both terminal and TMS-protected alkynes gave the products in one step. The beneficial effect of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 66 publications
(11 reference statements)
0
37
0
Order By: Relevance
“…Other methods of synthesis of CuCF 3 have been described: our choice has been fixed on a transformation of the derivative of silver which we already had for prior work. In the event of an optimization of the process, or that of an industrial synthesis, two routes of access to this reagent seem interesting to us: The direct generation of CuCF 3 from fluoroform, the advantages of which are certain (fluoroform is cheap and easily accessible, direct access to Cu CF 3 at ambient temperature and atmospheric pressure). However, fluoroform is a gas with a strong greenhouse effect, which limits its use. Preparation from trifluoromethyl sulfoxide, which is readily available or commercially available and which does not have the environmental disadvantages of fluoroform …”
Section: Resultsmentioning
confidence: 99%
“…Other methods of synthesis of CuCF 3 have been described: our choice has been fixed on a transformation of the derivative of silver which we already had for prior work. In the event of an optimization of the process, or that of an industrial synthesis, two routes of access to this reagent seem interesting to us: The direct generation of CuCF 3 from fluoroform, the advantages of which are certain (fluoroform is cheap and easily accessible, direct access to Cu CF 3 at ambient temperature and atmospheric pressure). However, fluoroform is a gas with a strong greenhouse effect, which limits its use. Preparation from trifluoromethyl sulfoxide, which is readily available or commercially available and which does not have the environmental disadvantages of fluoroform …”
Section: Resultsmentioning
confidence: 99%
“…The direct transformation of a C-H bond of terminal alkyne into a C-CF3 bond is one of the most efficient ways to construct C(sp)-CF3 bonds. Our first report in 2016 disclosed the trifluoromethylation of terminal alkynes using the "preoxidized" [CuCF3] from fluoroform (scheme 2), 8 which can be prepared from CuCl and t-BuOK with fluoroform on a large scale via a modified protocol based on Grushin's orignial preparation. 5 Starting from 1.0 equivalent of CuCl and 2.0 equivalents of t-BuOK, the mixture was stirred in degassed and dry DMF for 30 minutes, then bubbled with fluoroform gas for ~2 minutes.…”
Section: C(sp)-cf3 Bond Formationmentioning
confidence: 99%
“…[40][41][42][43][44][45] All these research groups showed that HCF3 can react with CuCl in the presence of t-BuOK and DMF, or zinc bis-2,2,6,6-tetramethylpiperidide (TMP)2Zn, 1,3-dimethylpropyleneurea (DMPU) and phenanthroline to produce fluoroform-derived CuCF3, which was a good trifluoromethylating reagent for the trifluoromethylation, 5,46,47 and afforded the desired products 25-27 in moderate to excellent yields. 40 18 F as the precursor of CuCF2 18 F was described by Vugts and co-workers (Scheme 12).…”
Section: Cucf3mentioning
confidence: 99%